Preparation and Flocculation Performance of Polyacrylamide Grafted Banana Stem Cellulose: Effect of Acrylamide and Ammonium Peroxydisulfate - Sperisa Distantina; Imanuel Daniel Nainggolan; Yosea Ido Fernando; Mujtahid Kaavessina (Program studi Teknik Kimia UNS, 2026)
ABSTRACT. Banana stem was identified as an attractive source of cellulose and a promising raw material for developing friendly bioflocculant hydrogels in water treatment. Polyacrylamide grafted banana stem cellulose (BS-g-PAA) was synthesized for flocculation application. The objective of this study was to investigate the effect of ammonium peroxydisulfate (APS) and acrylamide (AA) amount on the grafting efficiency and flocculation performance of obtained BS-g-PAA. In this study, 1 g banana stems flour was mixed in distilled water, followed by the addition of AA at different weight (10, 15, and 20 g) and APS at various weight (0.1, 0.15, and 0.2 g). The mixture was grafted using microwave irradiation at 540 W for 60 s per cycle, repeated for three cycles (total 180 s). The sample was then dried using an oven until constant weight and ground to obtain BS-g-PAA powder. The results of FTIR showed that the successful grafting of acrylamide onto the cellulose backbone. The grafting percentage increased with the increasing of AA amount, from 1,008% at 10 g AA to 2,098% at 20 g AA. Ammonium peroxydisulfate from 0.1 g to 0.2 g increased grafting percentage from 980% to 1,008%. BS-g-PAA hydrogel prepared by 1 g banana stem, 0.2 g APS, and 10 g AA produced the most effective turbidity reduction by reducing the turbidity value from 53.3 NTU of kaolin suspension to a final value of 15.29 NTU after 80 s flocculation test. These results demonstrated that hydrogels derived from banana stems may have promising potential as sustainable bioflocculants for wastewater treatment applications.Keywords:Banana stem, Ammonium peroxydisulfate, Acrylamide, Bioflocculant, Microwave grafting